(DITARIK) Aplikasi Sistem Billing pada Depo Kontainer: STUDY KASUS: PT. KAWASAN INDUSTRI MEDAN - Wahyudi, Eko; Rahmadhany, Denny; Firdaus, Muhammad Adi (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2020)
Following a rigorous, carefully concerns and communication between the publisher and the authors of the article published in Positif : Jurnal Sistem dan Teknologi Informasi to article entitled â€œAPPLICATION OF BILLING SYSTEMS IN CONTAINER DEPOTâ€ Vol 6, No 1, pp. 29-37, 2020. This paper has been withdrawn at the request of the author and has been retracted. The article contained redundant material, the author has informed editor that the paper was Accepted to published in another journal. The publisher apologizes to the authors and readers for the error and any inconvenience caused.